Properties Comparison of Open Hole and Non-Hole Carbon UD-Lycal Composite with Vacuum Bagging Manufacturing Method - Isna, Lathifa Rusita; Nugroho, Afid; P, Rezky Agung; R, Redha Akbar (BRIN Publishing, 2021)
Carbon fiber reinforce polymer is one of some composite materials that has the high strength with light weight material. To apply this composite to the amphibious airplane structure, it should through the experimental tensile test to know the tensile strength and modulus of elasticity of the composite. In this experiment, we use Carbon UD fiber and Lycal resin as the composite material that manufactured with Vacuum Bagging Method. Specimens and testing process refer to ASTM D3039 for non-hole specimen, and ASTM D5766 for open hole specimen of tensile test standard for composite matrix polymers. The result of the experimental test shows that the tensile modulus of elasticity for non-hole composite is 34.92 ± 0.13 GPa, with the Ultimate Tensile Strength of this composite is 1081± 0.03 MPa, and the modulus of elasticity for open hole composite is 41.87± 0.02 GPa, with the Ultimate Tensile Strength of this composite is 899.04± 0.02 MPa. The simulation yields nearly same stress-strain graph with the result of experiment. The result shows that, the open hole composite has the ultimate tensile strength lower than non-hole composite, it’s due to the open hole composite has a trigger failure that may decreasing the tensile strength value.